PUSAT KULINER KHAS KABUPATEN HULU SUNGAI SELATAN DI BANJARMASIN - Yulandha, Fitria Arissa; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Hulu Sungai Selatan has very interesting regional specialties to taste, but the popularity of the Hulu Sungai Selatan culinary specialty is less developed because people from various regions outside Hulu Sungai Selatan do not have enough time or opportunity to come directly to Hulu Sungai Selatan. At present the city that is a place to stay or settle is that most people from various islands, provinces and districts are Banjarmasin, in Banjarmasin there are actually places that sell typical Hulu Sungai Selatan culinary but unfortunately most only sell ketupat kandangan only while other cuisines are less popular , from that problem arises that is how to design a culinary center that can popularize the peculiarities of the Hulu Sungai Selatan culinary in Banjarmasin. To answer these problems a central culinary design can be used as a medium to popularize the typical Hulu Sungai Selatan culinary using the Peter Zumthor Atmospheres method emphasize the processing of the interior and exterior of the design and apply the design aspects of Peter Zumthor's Atmospheres themselves as a concept of design. At this culinary center only a few aspects are applied as concepts in interior and exterior design, this adjusts to the needs of the culinary center, the interior of the culinary center emphasizes the body of architecture aspects, material compatibility, between composure and seduction , levels of intimacy and the light on things in the dining, kitchen, gallery and culinary materials stores while on the exterior emphasizes compatibility, the temperature of the space, surrounding objects, tension between interior & exterior and the light on things on the outside buildings and sites. Thus, it is hoped that this culinary center will be able to become a media that can popularize the culinary specialties of Hulu Sungai Selatan.